LOCAL COMMUNITIES SAFETY IN THE CONTEXT THE RISE OF LONE-WOLF ACTIVITY - Jurczak, Justyna; Łachac, Tomasz (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2017)
The main aim of this article is to describe the phenomenon of so-called ‘lone-wolf’ activity in local communities as a number of attacks were recently carried out by individuals and small groups of people in various countries in the world. It seems that these are not incidental cases any more, but the phenomenon that will threaten the functioning of the state and societies. According to undertaken research a ‘lone-wolf’ attack mainly for political, social or religious reasons, that could differ in each community.